Students' Engagement with Learning Theory - Ingrid Schudel (Environmental Association of Southern Africa, 2005)
This paper reflects on a module on 'Teaching and Learning Interactions', presented as part of the Rhodes University Advanced Certificate in Education (Environmental Education).The module is designed to help students use theoretical logic to enhance (not replace) their practical logic of how teaching and learning takes place. Data was analysed from three teaching and learning activities in the module. After the first participatory activity on water and sanitation, students narrated what teaching and learning had taken place using language available from their prior experiences. In a second activity students were introduced to explanations of learning, provided by learning theorists. In the third activity students analysed a case study, using a variety of questions relating to teaching and learning. They then had to consider these same questions in the light of a participatory on-course teaching and learning activity. The paper reflects on how students have used understandings of the nature of reality, the construction of knowledge, the use of language, situated learning, action competence and social change, in order to narrate their teaching and learning experiences on the ACE(EE) course. Through this, the paper trials a reflexive approach to the teaching of learning theory in environmental education.